Brazil : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2014 Article IV Consultation highlights that Brazil's growth has decelerated in recent years. The boost from decade-old reforms, expanding labor income, and favorable external conditions, which enabled consumption and credit-led growth and underpinned sustained poverty reduction, has lost steam. Investment has been sluggish, reflecting eroding competitiveness, a worsening business environment, and lower commodity prices. The IMF staff projects negative output growth of 1 percent in 2015, with some drag from tighter fiscal and monetary policies and from the cuts in investment by Petrobras, adding to the downward momentum in activity carried over from 2014.